The Attitude of Project Managers Towards Project Management. A Multi-level Perspective - Jóhanna Ásta Þórarinsdóttir 1992- (2021)
The goal of this thesis is to get the perspective of project managers of project management in Iceland (macro), the perceived value of the profession in organizations (meso), and their personal opinion of the profession (micro). The overall goal was to see how project managers view their profession in whole. To find those answers, qualitative research was conducted with interviews with ten project managers from diverse sectors to get their opinion about the status of the profession in Iceland. The interviews were semi structured, and grounded theory was used. The researcher had prepared items but was also motivating and positive about discussing other aspects. The results show that project managers in Iceland feel that for the project manager's job to be considered a profession, there is a need for regulation so project managers can differentiate themselves from others that do not follow the methodology. How they differentiate themselves now is by getting a certification, most of the interviewees in this research thought it was important to have certification and renew it because it is the only current testament of skill. It seems that the profession is evolving and for people that are studying it now and, in the future, having the title chartered or regulated means it is worth the studying. That way, the profession can acquire proper recognition. Only time can tell if the profession gets more specific or if it will still be general like it is now. Markmið þessarar ritgerðar var að fá sjónarhorn íslenskra verkefnastjóra á verkefnastjórnun á Íslandi (macro), mikilvægi greinarinnar innan fyrirtækja (meso) og þeirra skoðun á greininni (micro). Til að komast að þessu var gerð eigindleg rannsókn með því að taka viðtöl við tíu verkefnastjóra á Íslandi úr mismunandi geirum til að segja skoðun sína á stöðu verkefnisstjórnunar á Íslandi. Viðtölin voru hálf opin þar sem rannsakandi hafði gert spurningalista í anda grundaðrar kenningar, en var einnig opinn fyrir því að ræða hluti meira eftir því sem viðmælendur vildu. ...